The Mix Between Pay-as-you-go and Funded Pensions and What Demography Has to Do with it - Bernard M.S. van Praag; Pedro Cardoso (Center for Economic Studies and ifo Institute (CESifo), 2003)
A model is presented that explains the mix between funded and unfunded pension systems. It turns out that total pension and the relative shares of the two systems may be explained and are determined by the population growth rate, technological growth, the time-preference discount rate, that relative risk aversion, the production function, and the political representation of the old. A fall in the population growth rate, even to negative values, will imply a reduction of the interest rate and an increase in the capital-output ratio. Whether the pension system will shift to more or less funding depends on the political weight of the elderly. If the elderly succeed in getting more weight in the political process if their population share increases, which is likely when the population shrinks, the accent on the PAYG- system will increase. A fall in the population growth rate will result in a reduction of average welfare. This reduction is more severe, the larger the political power of the elderly.
Keywords: 330; old-age pensions; pay-as-you-go; intergenerational transfers; retirement benefits